Doing Business in Russia from the Perspective of a Czech Company - Remizov, Gleb; Halík, Jaroslav, 1961-; Štěrbová, Ludmila, 1957-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
This bachelor thesis focuses on doing business in Russia from the perspective of a Czech company. The main objective is to depict the business environment of Russia and its beer market for a Czech beer company. The first part concentrates on general information about Russia and a specific sector of its economy. Second part focuses on the conditions of entry to the Russian beer market, risks and opportunities for a Czech company. In the third part there is a summary of a research and relevant conclusions to it.
Vedoucí práce: Jaroslav Halík
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses